The effect of contextual advertising on e-engagement with content relevance as mediation: Survey on Kienka official Instagram followers - Wibowo, Lili Adi; Aulia Nurizky, Sherly; Dirgantari, Puspo Dewi; Suhud, Usep; Qudratov, Inomjon (Jurnal Siasat Bisnis, 2025)
Purpose – This study aims to obtain an overview and analyze the influence of contextual advertising on e-engagement with Content Relevance as a mediating variable on Kienka Official Instagram followers. Design/methodology/approach – This research is descriptive and verification with a quantitative approach. The sampling technique uses simple random sampling with 348 respondents. Data is processed statistically using the Structural Equation Modeling (SEM) method with the help of the AMOS for Windows program. Findings – The study results indicate that contextual advertising positively and significantly influences e-engagement with Content Relevance as a mediating variable. The magnitude of the critical ratio value that is greater than the minimum value indicates a significant influence simultaneously. The better the company pays attention to contextual advertising through Content Relevance, the higher the e-engagement produced. The dimension of contextual advertising with the highest contribution in forming e-engagement is effectiveness, while the lowest is visual experience. Meanwhile, the dimension of Content Relevance that contributes the most to increasing e-engagement is dynamism activity, while the lowest is topical relevance. Research limitations/implications – This study only focuses on Kienka Official Instagram followers so the results may not be generalizable to other platforms or industries. Further studies can explore additional factors that influence e-engagement and test the research model on different types of digital platforms and different business sectors. Practical implications – The results of this study provide insight for companies in optimizing contextual advertising and Content Relevance strategies to increase e-engagement. Companies are advised to emphasize the effectiveness aspect in contextual advertising and strengthen dynamism activity in Content Relevance to increase audience interaction more effectively. Originality/value – This study provides a new contribution by revealing the role of Content Relevance as a mediator in the relationship between contextual advertising and e-engagement. The results can be a reference for academics and practitioners in developing more effective digital marketing strategies based on contextual advertising and Content Relevance.